Penggunaan Metode Creative Problem Solving (CPS) Dalam Meningkatkan Keterampilan Siswa Pada MataPelajaran Fisika Di SMAN 10 Kota Jambi - Evi Ramna Farni (STIT Muhammadiyah Paciran Lamongan, 2020)
AbstractStudent at X grade MIPA I in even semester learn about the second motion law that talks about momentum and stylistic changes in physics. The students ' level of knowledge in this material is very low, characterized by the average skills of receiving, analyzing, and operationalizing the second law of motion only 25.42%. In an effort to increase the average of the skills of accepting, analyzing and operationalizing the second motion law, it is necessary to take action by applying the creative problem Solving (CPS) method to the learning activities. The first action on the first sikulus showed the average skills of grade X students I had increased by 17.49%, while on the second cycle increased from